Salaried Strata Investment Behavior towards Financial Products-Review and Prospects for Future Research - Dahiya, Monika; Chaudhary, Bhuvnender (International Research Journal of Management, IT & Social Sciences, 2016)
The financial surface of the globe at all times reveals a weird balanced impact of the public investment preferences, their understanding about the investment requirements, their anticipation of returns on their investments etc. Perhaps forecasting the growth of the business world would be crucial without an apposite comprehension of the investment behavior of the key part of the society called salaried class. This paper covers appraisal of various financial instruments like equity/stocks, term deposits in banks, kisan vikas patra, national savings certificate, insurance policies, mutual fund and converse the factors persuading investment decision process. The major factors influencing the financial investment behavior are demographic factors (like age, income, qualification, gender, etc.) and socio-economic factors (like family income, tax benefits, safety of fund, risk inclination, return on investment). This study aims to serve a channel to the need of a comprehension of the financial objectives of the salaried class investors with that of their determined desire for the investment returns. Certainly, this information could unwrap the prospect of predicting even the future of Indian Economy itself besides, providing span to fine-tuning the investment prudence of the public towards progressive and fruitful choices for themselves and the nation.